Stakeholder Influence on Malawi's Digital Economy Strategy Execution - Muu, Nguyen Thanh (Journal of Global Economy, Business and Finance, 2025)
This article explored the influence of key stakeholders on the execution of Malawi’s Digital Economy Strategy. Government of Malawi introduced the 2021 - 2026 Malawi Digital Economy Strategy (MDES) in February, 2021 through the National Planning Commission of Malawi (NPCM). The main objective of the MDES is to create inclusive wealth which offers Malawians access to a prosperous economy. The five years strategy aims at improving connectivity and improves internet access from 14% to 80% by the year 2026. In addition, the strategy aims at providing affordable internet by cutting out taxes. In the article, a qualitative approach was used, under the guidance of the Stakeholder theory. The researcher purposively sampled five (5) Senior Public Officers from the E- government Department, four (4) Senior Public Officers from Public Sector Reforms Management Department (PSRMD) and three (3) Senior Public Officers from the Ministry of Information (MoI). Data was collected through Key Informant Interviews (KIIs) and secondary sources. Thematic analysis was used to analyze the results. The results show that the key stakeholders play a very significance role in implementation of the MDES because they help in the achievement of the intended goals and objectives. However, this is somehow affected due to challenges such as: a lack of proper coordination and collaboration among the key stakeholders. The study results are of great significance in creating new knowledge which will assist in the effective implementation of the MDES.